Control system of a performance test-bed for frost protection wind machines - Yongguang, Hu; Ping, Liu; Amoah, Asante Eric; Wenye, Wu; Pingping, Li (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: To test the performance and optimize operational parameters of various frost protection wind machines, a control system of performance test-bed was designed and developed based on Programmable Logic Controller (PLC) and touch screen. The system realized automatic control of operational parameters including hydraulic platform height, impeller rotation speed, depression angle, rotation range and cycle. Field case study results shows that the control accuracy of all the parameters was achieved with the average errors of 2.11 cm for height, 9.5 r/min for impeller rotation speed, 0.83° for pan-tilt rotation range and 0.061 min for rotation cycle. With the control of the test-bed, the performances of various wind machines, such as the distribution of airflow and temperature, and frost protection effect, could be tested under various working conditions, which provide experiment supports for developing wind machines adapted to different conditions with higher frost protection effect. Keywords: frost protection, wind machines, performance test-bed, design, control, PLC DOI: 10.3965/j.ijabe.20160906.1664 Citation: Hu Y G, Liu P, Asante E A, Wu W Y, Li P P. Control system of a performance test-bed for frost protection wind machines. Int J Agric & Biol Eng, 2016; 9(6): 36－43.